Impact of sleep deprivation on the outcomes of percutaneous coronary intervention. Issue 6 (3rd January 2018) - Iverson, Ann; Stanberry, Larissa; Garberich, Ross; Antos, Amber; Sandoval, Yader; Burke, M. Nicholas; Chavez, Ivan; Gössl, Mario; Henry, Timothy D.; Lips, Daniel; Mooney, Michael; Poulose, Anil; et al.
Abstract: Objectives: This study sought to compare the clinical outcomes of percutaneous coronary interventions (PCIs) performed by sleep deprived and non‐sleep deprived operators. Background: Interventional cardiologists are at risk for sleep deprivation as they often have to perform emergent procedures at night, but the effects of sleep deprivation on clinical outcomes have received limited study. Methods: We examined the frequency, clinical characteristics, and outcomes of daytime PCIs performed by sleep deprived and non‐sleep deprived operators at a tertiary medical center. Operators were considered sleep deprived when performing a daytime (7 am–11:59 pm) procedure preceded by a nighttime (12 am–6:59 am) procedure on the same date. Results: Of the 12, 680 daytime PCIs performed from 6/29/09 to 12/30/2016, 367 (2.9%) were performed by sleep deprived operators. Patients undergoing PCI performed by a sleep deprived operator were more likely to be younger, white, and to present with ST‐elevation acute myocardial infarction (STEMI). The incidence of in‐hospital death (1.1% vs. 1.3%, P = 1.0) and bleeding within 72 hr (3.9% vs. 2.9%, P = 0.29) were similar for procedures performed by sleep‐deprived and non‐sleep deprived operators. When the sleep deprived group was further stratified based on degree of sleep deprivation or length of sleep interruption, differences in mortality and total bleeding remained non‐significant. Conclusions: In this large single center study, operator sleep deprivation did not appear to adversely impact PCI outcomes.